The Enigma Girls: How Ten Teenagers Broke Ciphers, Kept Secrets, and Helped Win World War II - Fleming, Candace (New York : Scholastic Focus, 2024)
""You are to report to Station X at Bletchley Park, Buckinghamshire, in four days time....That is all you need to know." This was the terse telegram hundreds of young women throughout the British Isles received in the spring of 1941, as World War II raged. As they arrived at Station X, a sprawling mansion in a state of disrepair surrounded by Spartan-looking huts with little chimneys coughing out thick smoke-these young people had no idea what kind of work they were stepping into. Who had recommended them? Why had they been chosen? Most would never learn all the answers to these questions. Bletchley Park was a well-kept secret during World War II, operating under the code name Station X. The critical work of code-cracking Nazi missives that went on behind its closed doors could determine a victory or loss against Hitler's army. Amidst the brilliant cryptographers, flamboyant debutantes, and absent-minded professors working there, it was teenaged girls who kept Station X running. Some could do advanced math, while others spoke a second language. They ran the unwieldy bombe machines, made sense of wireless sound waves, and sorted the decoded messages. They were expected to excel in their fields and most importantly: know how to keep a secret"
Keywords: World War, 1939-1945 -- Juvenile literature -- Cryptography; Enigma cipher system -- Juvenile literature; World War, 1939-1945 -- Juvenile literature. -- Military intelligence -- Great Britain